16 Piloting a fully immersive in-situ simulation teaching course for final year medical students: 'carry the bleep'. (17th November 2016) - Yiangou, A; Kamalanathan, S; Altemimi, B; Mercer, SJ
Abstract : Background: Recent evidence in the literature has shown that medical students across different medical schools have similar preparation for starting the first work post. 1, 2 Almost half of students feel that they are not adequately prepared, mainly concerned with being on call, clinical prioritisation, management of acutely unwell patients, prescribing, time management, paper work and ward work. 2 These concerns still exist despite changes to the curriculum including junior doctor shadowing and simulation training. 3 We have designed and implemented a pilot teaching course for final year medical students from the University of Liverpool to simulate 2 days being a junior doctor on call, "Carry the Bleep". Methodology: A total of 8 final year medical students were given a bleep to carry over a 2-day period at our institution. During normal working hours, students were bleeped to attend clinical tasks sometimes simultaneously. A total of 12 stations were designed with faculty simulating the roles of health care professionals and patients. Stations addressed communication, clinical and practical skills, drug prescription and 2 'in-situ' high fidelity simulation scenarios. Structure debrief was provided immediately after each station. Feedback forms were completed by students at the start and end of the course to assess confidence and attitudes. Results: The student feedback received was extremely positive as reported qualitatively and quantitatively. There were increases in confidence to start as a Foundation Doctor including clinical and communication skills, usefulness and value of such a course including high-fidelity simulations and awareness of the on call duties of a Foundation Doctor. Conclusions and recommendations: Following the successful pilot of the course where Final Year Medical Students carry a bleep and have to respond to typical scenarios and problems experienced by a Foundation Doctors, we intend to offer this training to all Final Year Students next year. References: Illing J, Morrow G, Kergon C, Burford B, Spencer J, Peile E, Davies C, Baldauf B, Allen M, Johnson N, Morrison J, Donaldson M, Whitelaw M, Field, M. 'How prepared are medical graduates to begin practice? a comparison of three diverse UK medical schools. Final report to GMC April 2008. Project Report. DU 2008. Illing JC, Morrow GM, Rothwell nee Kergon CR, Burford BC, Baldauf BK, Davies CL, et al . Perceptions of UK medical graduates' preparedness for practice: A multi-centre qualitative study reflecting the importance of learning on the job. BMC Medical Education 2013;13 (1):1–12. Cave J, Goldacre M, Lambert T, Woolf K, Jones A, Dacre J. Newly qualified doctors' views about whether their medical school had trained them well: questionnaire surveys. BMC Medical Education . 2007;7 (1):1–6.